New Data Define the Molecular Phylogeny and Taxonomy of Four Freshwater Suctorian Ciliates With Redefinition of Two Families Heliophryidae and Cyclophryidae (Ciliophora, Phyllopharyngea, Suctoria) - Ma, Mingzhen; Li, Yuqing; Yuan, Qingxiang; Zhao, Xuetong; Al-Rasheid, Khaled A. S.; Huang, Jie; Ma, Honggang; Chen, Xiangrui (Frontiers in Microbiology, 2021)
Four suctorian ciliates, Cyclophrya magna Gönnert, 1935, Peridiscophrya florea (Kormos & Kormos, 1958) Dovgal, 2002, Heliophrya rotunda (Hentschel, 1916) Matthes, 1954 and Dendrosoma radians Ehrenberg, 1838, were collected from a freshwater lake in Ningbo, China. The morphological redescription and molecular phylogenetic analyses of these ciliates were investigated. Phylogenetic analyses inferred from SSU rDNA sequences show that all three suctorian orders, Endogenida, Evaginogenida and Exogenida, are monophyletic, and that the latter two clusters as sister clades. The newly-sequenced P. florea forms sister branches with C. magna, while sequences of D. radians group with those from H. rotunda within Endogenida. The family Heliophryidae, which is comprised of only two genera, Heliophrya and Cyclophrya, was previously assigned to Evaginogenida. There is now sufficient evidence, however, that the type genus Heliophrya reproduces by endogenous budding, which corresponds to the definitive feature of Endogenida. In line with this, and with the support of molecular phylogenetic analyses, we therefore transfer the family Heliophryidae with the type genus Heliophrya to Endogenida. The other genus, Cyclophrya, still remains in Evaginogenida because of its evaginative budding. Therefore, combined with morphological and phylogenetic analysis, Cyclophyidae are reactivated, and it belongs to Evaginogenida.